Människan förändrar religionen - Sandell, Josefin (Uskonnontutkija - Religionsforskaren, 2015)
Bokrecension av Mika T. Lassander 2014. Post-materialist religion: Pagan Identities and Value Change in Modern Europe. Bloomsbury, London, 201 s.